Flow-based method for the determination of biomarkers urea and ammoniacal nitrogen in saliva - Thepchuay, Yanisa (2020)
Salivary urea and ammonium levels are potential biomarkers for chronic kidney disease. A fast and efficient assessment of these compounds in the saliva of healthy and diseased individuals may be a useful tool to monitor kidney function. Materials & methods: Ammonium ions were measured with an ammonia selective electrode after conversion to ammonia gas. A urease reactor was incorporated in the manifold to hydrolyze urea to ammonium, thereby providing values of ammonia from both urea and ammonium ions in the sample. The accuracy of the method was assessed by comparison with a commercially available kit for urea and ammonium determination. Conclusion: A sequential injection method for the biparametric determination of salivary urea and ammonium employing a single sequential injection manifold was successfully applied to samples collected from both healthy volunteers and chronic kidney disease patients.